Linking Earthquake Magnitude‐Frequency Statistics and Stress in Visco‐Frictional Fault Zone Models. Issue 20 (12th October 2022) - Beall, Adam; van den Ende, Martijn; Ampuero, Jean‐Paul; Capitanio, Fabio A.; Fagereng, Åke
Abstract: The ability to estimate the likelihood of given earthquake magnitudes is critical for seismic hazard assessment. Earthquake magnitude‐recurrence statistics are empirically linked to stress, yet which fault‐zone processes explain this link remains debated. We use numerical models to reproduce the interplay between viscous creep and frictional sliding of a fault‐zone, for which inter‐seismic locking becomes linked to stress. The models reproduce the empirical stress‐dependent earthquake magnitude distribution observed in nature. Stress is related to the likelihood a fault section is near frictional failure, influencing likely rupture lengths. An analytical model is derived of a fault consisting of identical patches, each with a probability of inter‐seismic locking. It reproduces a similar magnitude‐recurrence relationship, which may therefore be caused by probabilistic clustering of locked fault patches. Contrasts in earthquake statistics between regions could therefore be explained by stress variation, which has future potential to further constrain statistical models of regional seismicity. Plain Language Summary: The frequency of earthquakes with a given magnitude is empirically described by the Gutenberg‐Richter law, where large earthquakes occur less frequently than small ones. Variations in magnitude distribution between regions have been correlated with the tectonic force acting on a fault. However, it is unclear which mechanism is responsible for this relationship, restricting its predictive capability. Here, we create computational models in which some portions of a fault can generate earthquakes and others can move slowly (not generating earthquakes). This slow movement acts to relax and limit the elastic forces that build up around the fault. This approach is used to reproduce realistic earthquake statistics, indicating that processes that limit the stress build‐up between earthquakes may be responsible for the varying likelihoods of earthquake magnitudes observed in nature. Key Points: Combining viscous creep and rate‐and‐state friction in fault slip models limits the peak loading stress over the earthquake cycle Numerical and analytical models reproduce Gutenberg‐Richter earthquake size‐recurrence statistics, with a b ‐value linked to fault stress The interplay between loading stress and probabilistic fault locking provides an explanation for regional contrasts in b ‐value